Why do they (still) sing stories? Singing narratives in Tanjung Bunga (eastern Flores, Lamaholot, Indonesia) - Rappoport, Dana (Wacana, Journal of the Humanities of Indonesia, 2016)
In eastern Flores, on the Tanjung Bunga peninsula (among Western Lamaholot speakers), several times a year, ritual narratives (opak) are performed on a square dancing area, where all the clans of the same ceremonial land meet. Three types of narrative are sung, according to three kinds of rituals. The article explains the context, content and performance details of these stories, performed all night long. Why do the various clans continue to sing all these narrative? What values do these long poems have for people who sing them? Until now, studies on this subject have been remarkably few, and not even a partial transcription or translation of these narratives is available. This article offers a preliminary insight into these sung narratives, to show how vital they still are in eastern Flores.